THE ROLE OF THE GOVERNMENT IN ASSISTANCE IN THE DEVELOPMENT OF OYSTER MUSHROOM BUSINESSES TO IMPROVE THE ECONOMY OF THE VILLAGE COMMUNITY BLOK 10 DOLOK MASIHUL DISTRICT - Hastuti Handayani Harahap; Indra Welly Arifin; Frederick Rudy Sentosa Rajagukguk (RADJA PUBLIKA, 2024)
This research aims to describe the role of the government in assisting the development of the oyster mushroom business to improve the economy of the village community in Block 10, Dolok Masihul District. This research uses a qualitative method with a case study approach. The data collection method used was observation, interviews, documentation, and the analytical processing technique used was descriptive qualitative. Coordination and Discussion: The PKM team coordinates and discusses with partners to understand their needs and problems in developing the business. Support and attention from various parties, especially related government institutions, is very important for small and medium enterprises (MSMEs) such as these PKM partners. Implementation of the Domas Oyster Mushroom (Jatiramdo) business development strategy is carried out through programs or activities such as increasing the number of special memberships for oyster mushroom farmers, increasing member innovation and creativity, socialization and guidance programs, and purchasing unsold harvests. The implementation of the Domas Oyster Mushroom (Jatiramdo) business development strategy can be said to be successful, the members admitted that there was an increase in knowledge and skills in the agricultural sector, obtained new information about agriculture, and the members became creative and innovative members in terms of processed oyster mushroom products.